Characterization of OXA-29 from Legionella (Fluoribacter) gormanii: Molecular Class D β-Lactamase with Unusual Properties - Franceschini, Nicola (American Society for Microbiology, 2001)
A class D β-lactamase determinant was isolated from the genome of Legionella (Fluoribacter) gormanii ATCC 33297(T). The enzyme, named OXA-29, is quite divergent from other class D β-lactamases, being more similar (33 to 43% amino acid identity) to those of groups III (OXA-1) and IV (OXA-9, OXA-12, OXA-18, and OXA-22) than to other class D enzymes (21 to 24% sequence identity). Phylogenetic analysis confirmed the closer ancestry of OXA-29 with members of the former groups. The OXA-29 enzyme was purified from an Escherichia coli strain overexpressing the gene via a T7-based expression system by a single ion-exchange chromatography step on S-Sepharose. The mature enzyme consists of a 28.5-kDa polypeptide and exhibits an isoelectric pH of >9. Analysis of the kinetic parameters of OXA-29 revealed efficient activity (k(cat)/K(m) ratios of >10(5) M(−1) · s(−1)) for several penam compounds (oxacillin, methicillin, penicillin G, ampicillin, carbenicillin, and piperacillin) and also for cefazolin and nitrocefin. Oxyimino cephalosporins and aztreonam were also hydrolyzed, although less efficiently (k(cat)/K(m) ratios of around 10(3) M(−1) · s(−1)). Carbapenems were neither hydrolyzed nor inhibitory. OXA-29 was inhibited by BRL 42715 (50% inhibitory concentration [IC(50)], 0.44 μM) and by tazobactam (IC(50), 3.2 μM), but not by clavulanate. It was also unusually resistant to chloride ions (IC(50), >100 mM). Unlike OXA-10, OXA-29 was apparently found as a dimer both in diluted solutions and in the presence of EDTA. Its activity was either unaffected or inhibited by divalent cations. OXA-29 is a new class D β-lactamase that exhibits some unusual properties likely reflecting original structural and mechanistic features.